Three Dimensional Printing Bilayer Membrane Scaffold Promotes Wound Healing - Wang, Shoubao; Xiong, Yao; Chen, Jingting; Ghanem, Abdulsamad; Wang, Yinmin; Yang, Jun; Sun, Binbin (Frontiers in Bioengineering and Biotechnology, 2019)
Full-thickness skin wounds are common and could be a heavy physical and economic burden. With the development of three dimensional (3D) printing technology, skin-like constructs have been fabricated for skin wound healing and regeneration. Although the 3D printed skin has great potential and enormous advantages before vascular networks can be well-constructed, living cells are not recommended for 3D skin printing for in vivo applications. Herein, we designed and printed a bilayer membrane (BLM) scaffold consisting of an outer poly (lactic-co-glycolic acid) (PLGA) membrane and a lower alginate hydrogel layer, which respectively mimicked the skin epidermis and dermis. The multi-porous alginate hydrogel of the BLM scaffolds promoted cell adhesion and proliferation in vitro, while the PLGA membrane prevented bacterial invasion and maintained the moisture content of the hydrogel. Skin regeneration using the bilayer scaffold was compared with that of PLGA, alginate hydrogel and the untreated defect in vivo. Tissue samples were analyzed using histopathological and immunohistochemical staining of CD31. In addition, mRNA expression levels of collagen markers [collagen type 1 alpha 1 (COL1a1) and collagen type 3 alpha 1 (COL3a1)] and inflammatory markers [interleukin-1β (IL-1β), as well as tumor necrosis factor (TNF-α)] were measured. Conclusively, the application of BLM scaffold resulted in highest levels of best skin regeneration by increasing neovascularization and boosting collagen I/III deposition. Taken together, the 3D-printed BLM scaffolds can promote wound healing, and are highly suitable for a wide range of applications as wound dressings or skin substitutes.